2021
DOI: 10.1038/s41598-021-95331-w
|View full text |Cite
|
Sign up to set email alerts
|

Mortality during tuberculosis treatment in South Africa using an 8-year analysis of the national tuberculosis treatment register

Abstract: In 2011, the South African HIV treatment eligibility criteria were expanded to allow all tuberculosis (TB) patients lifelong ART. The impact of this change on TB mortality in South Africa is not known. We evaluated mortality in all adults (≥ 15 years old) treated for drug-susceptible TB in South Africa between 2009 and 2016. Using a Cox regression model, we quantified risk factors for mortality during TB treatment and present standardised mortality ratios (SMR) stratified by year, age, sex, and HIV status. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…The TB mortality rate remained relatively constant from 2016 to 2020 in this study, with no specific trend. A South African study reported a slightly low cumulative mortality rate of 8.6% for adult patients who initiated drug-susceptible TB treatment ( Osman et al., 2021 ). The TB mortality rate in Thaba-Tseka district does not meet the 2020 ‘End TB strategy’ target of a 35% reduction in mortality rate from 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The TB mortality rate remained relatively constant from 2016 to 2020 in this study, with no specific trend. A South African study reported a slightly low cumulative mortality rate of 8.6% for adult patients who initiated drug-susceptible TB treatment ( Osman et al., 2021 ). The TB mortality rate in Thaba-Tseka district does not meet the 2020 ‘End TB strategy’ target of a 35% reduction in mortality rate from 2015.…”
Section: Discussionmentioning
confidence: 99%
“…However, among HIV-negative females in China, tuberculosis mortality risks were higher in younger groups, quite similar to the trends reported in Spain and Hong Kong. Osman et al 33 explained that younger females might have few other causes of death, and the proportion of other causes of death increased in the older age group. In China, the prevalence of malnutrition among women aged 15-24 years was the highest among women aged 15-49 years, 34 which could lead to a decrease in immunity and an increased risk of tuberculosis infection and death.…”
Section: Discussionmentioning
confidence: 99%
“…For mortality, the M:F ratio reduced to 0.93 (i.e., higher mortality in females). This is possibly because females' 'background' mortality (deaths not related to HIV and tuberculosis, e.g., due to violence) is much lower than in males 31,37 ; and therefore, more females survive to older ages than males. In our model we assumed tuberculosis mortality rates increase with age (Table 1), people in older age groups (55 + years) contribute disproportionately to tuberculosis mortality, and the majority are likely females.…”
Section: Discussionmentioning
confidence: 99%
“…In our model we assumed tuberculosis mortality rates increase with age (Table 1), people in older age groups (55 + years) contribute disproportionately to tuberculosis mortality, and the majority are likely females. The lower female background mortality rates may also explain why in females compared to males, tuberculosis mortality may appear higher relative to background mortality 31 , although their absolute tuberculosis mortality risk is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation